P1-S2.66 Risk assessment in a large cohort of urban public high school students infected with CT or GC: Philadelphia, 2009−2010. (10th July 2011) - Lewis, F; Mettey, A; Anschuetz, G; Asbel, L; De Los Reyes, A; Salmon, M
Abstract : Background: Since 2003, the Philadelphia Department of Public Health (PDPH) has run an in-school education, testing, and treatment program for gonorrhoea (GC) and Chlamydia (CT) at all public high schools; however, GC/CT positivity rates have not declined over time, and risk factors for infection in this population are unknown. To explore the issue, we standardised data collection and partner services interviews in an attempt to identify students at high risk for GC/CT. Methods: For the 2009−2010 school year, all students were asked if they ever had sex, and students who tested positive for GC/CT were asked a few additional questions about their risk at time of in-school treatment by PDPH. Student specimens were confidentially obtained and processed. Answers from interviewed students were compared with reportable disease records. Results: Of ∼31 800 students attending a presentation, 14 031 (∼44.1%) tested; of these, 8674 (61.8%) reported ever having sex, 2316 (16.5%) reported no sex, and 2950 (21.0%) did not answer. GC/CT positivity was higher for students who did not answer (8.5%) and those who reported having sex (7.5%) than for students who reported no sex (0.8%). Infected students were significantly more likely to be black: 8.9% of blacks were infected compared with 2.2% of whites (p<0.0001). 926 students tested positive and 564 (60.9%) were interviewed (Abstract P1-S2.66 table 1 ); of these, 169 (30%) had ≥2 sex partners in the past 60 days, 121 (21.5%) had been arrested, and 70 (17.9% of females) had been pregnant. Though only 72 (12.8%) interviewed students reported a previous STD, 130 (23.0%) had a documented history of GC/CT in the PDPH database. Compared to females, males reported earlier sexual initiation, had a greater percentage report first sex before age 13, and took twice as long from sexual initiation to first STD (Abstract P1-S2.66 table 1 ). Interviewed black (compared with white) students were more likely to report a history of pregnancy, STD, and arrest, though these differences were not statistically significant. Conclusions: A striking proportion of students who test positive in the PHSSSP are black, have high partner number, young age at first sex, and past STD, pregnancy, and/or arrest. Some of these factors probably predispose students to future STD. PDPH is working to develop behavioural interventions for this population to address ongoing risk; as many students report young age at sexual initiation, interventions that begin before high school should also be investigated.